Preliminary observations on the agricultural economy of Dvin - Hovsepyan, Ruben (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
The city of Dvin was one of the largest craft and trade centers of medieval Armenia. The agricultural economy of the city of Dvin is briefly researched for the first time based on the medieval Armenian (Sebeos, Hovhannes Draskhanakerttsi), Arabic (ibn-Haukal, Istahri), Byzantine (Procopius of Caesarea, Hovhannes Skilitzes), and Ottoman (Munajjim-Bashi) sources, as well as archaeological material related to agriculture found during the excavations of Dvin over the years. We can state that agriculture played a certain role in the economy of the city of Dvin. Of course, it is still too early to say what place the agricultural economy occupied in the life of the city, how widespread it was. Around the city was an agricultural zone with vineyards, orchards, and arable land, which are mentioned in medieval sources. The evidence of rice cultivation is especially important. Archaeological objects also testify to agricultural activities in the city.